Rapid quantification of acetaminophen in plasma using solid‐phase microextraction coupled with thermal desorption electrospray ionization mass spectrometry. (4th November 2019) - Shiea, Jentaie; Bhat, Suhail Muzaffar; Su, Hung; Kumar, Vinoth; Lee, Chi‐Wei; Wang, Chin‐Hsiung
Abstract : Rationale: Solid‐phase microextraction coupled with thermal desorption electrospray ionization tandem mass spectrometry (SPME‐TD‐ESI‐MS/MS) is proposed as a novel method for the rapid quantification of acetaminophen in plasma samples from a pharmacokinetics (PK) study. Methods: Traces of acetaminophen were concentrated on commercial fused‐silica fibers coated with a polar polyacrylate (PA) polymer using direct immersion SPME. No agitation, heating, addition of salt, or adjustment of the pH of the sample solution was applied during the extraction. Any acetaminophen absorbed on the SPME fibers was subsequently desorbed and detected by TD‐ESI‐MS/MS. Results: Parameters of the absorption, sensitivity, reproducibility, and linearity for the SPME‐TD‐ESI‐MS/MS method were evaluated. The time required to complete a TD‐ESI‐MS/MS analysis was less than 30 seconds. Matrix‐matching calibration was performed to calculate the concentration of acetaminophen in the sample. A linear calibration curve with a concentration range of 100–10, 000 ng/mL was constructed to calculate the quantity of acetaminophen. The SPME‐TD‐ESI‐MS quantification results for acetaminophen in plasma were in good agreement with those obtained by the conventional LC/MS/MS method. Conclusions: With the proposed method, a 10‐min SPME time was enough to achieve the lower limit of quantitation (i.e. 100 ng/mL) and for a complete PK profiling of acetaminophen. A shorter extraction time could be achieved by applying agitation, heating, adding salt, or adjusting the pH of the sample solution to enhance analyte absorption efficiency. The time required to detect acetaminophen on the SPME fiber was less than 30 s, allowing the rapid quantification of acetaminophen in plasma with good accuracy.